Glacier surging controls glacier lake formation and outburst floods: The example of the Khurdopin Glacier, Karakoram - Bazai, Nazir Ahmed; Cui, Peng; Liu, Dingzhu; Carling, Paul A.; Wang, Hao; Zhang, Guotao; Li, Yao; Hassan, Javed (Global and Planetary Change, 2022)
Ice dammed glacial lake outburst floods (GLOFs) associated with surge glaciers are increasing in response to climate change. Predicting the phenomenon to protect downstream communities remains challenging around the globe. Surge-type glaciers are characterized by unsteady movements and frequent frontal advances, which cause natural hazards by obstructing river channels, forming ice-dammed lakes, which can cause GLOFs, posing threats downstream. The determination of the surge characteristics, timing and evolution of lakes and GLOFs is fundamental to flood control and disaster management. In this study, the case of the Khurdopin Glacier (Karakoram) is used to elucidate key behavioral characteristics of surging glaciers that usefully can be applied to understand the GLOF hazard from glaciers worldwide. Seven surge periodical cycles associated with the Khurdopin Glacier that occurred at intervals of 19-20 years between 1880 and 2020 were investigated using a GLOF dataset. The ice flow dynamics of three surge events that occurred between 1970 and 2020 were analyzed using high-resolution satellite imagery. The results indicate that the maximum and minimum surge velocities control the conduit development that drains lakes resulting in a number of GLOFs. A surge between 1998 and 2002 generated six GLOFs. A subglacial drainage model was developed to estimate the timing of the peak discharge in GLOF hydrographs. The results show that conduit melt enlargement becomes the dominant drainage process at one-third of the rising limb. These floods' high peak discharges and short durations are primarily due to the higher lake water temperature, which controls the conduit enlargement rate. Based on the current study results, the proposed model can be adopted worldwide for surge-type glaciers. The initiation of the main surge period, which leads to lake formation, can be anticipated, as the pre-surge period can be identified using remote-sensing analysis. The timing of ice-dammed lake formation and GLOFs can be estimated, providing ...